Pengembangan Wearable Device untuk Monitoring dan Tracking Pasien Isoman Covid-19 Berbasis Mobile - Dina Angela; Hans Melkisedek Simanjuntak; Hanif Fakhrurroja (Website, 2022)
Reducing the spread of the Covid-19 virus and handling every patient affected by Covid-19 are the main targets of the Indonesian government in dealing with the current pandemic. It takes cooperation between individuals. For example, between health workers and patients who are undergoing independent isolation (isoman) due to being infected with Covid-19. Body temperature, heart rate, blood oxygen levels, and patient movement are the main parameters of a Covid-19 patient that must be routinely checked and monitored by health workers. Patients in self-isolation also need to monitor their health conditions while undergoing isolation. Besides being routine, examination and monitoring of the condition of isoman patients also need to be carried out continuously because the patient's condition can change at any time. In this study, a mobile-based wireless Covid-19 patient condition monitoring system was developed so that monitoring can be carried out remotely. This system uses MCP9808 as body temperature, MAX30100 as a sensor for heart rate and blood oxygen levels, and GPS as a sensor for patient movement in isolation locations. The data obtained from each of these sensors will be sent wirelessly to the cloud database using the NodeMCU ESP8266. The data received in the cloud database is displayed in real-time on a mobile-based dashboard and analyzed to obtain information on the progress of the patient's condition. This system is to assist health workers in monitoring the condition of Covid-19 patients remotely and help self-isolated patients to monitor their health without always having direct contact with health workers. Health workers are facilitated to find out the tendency of the patient's condition so that they can make the right decisions and actions.